Persuasion Strategy in Religious Discourse About Genocide in Palestine on Instagram - Adinda Afifah Anwar; Sukarno Sukarno; Santuso Santuso (Journal of Islamic Education and Intellectual Discourse (JIED), 2025)
Persuasive language is widely used in religious discourse on social media to influence public perception and action, particularly in humanitarian issues such as the genocide in Palestine. In this context, rhetorical strategies play a crucial role in shaping support and solidarity. Purpose: This study aims to identify and describe the persuasion strategies employed in religious discourse about the Palestinian genocide on Instagram, and to explain how linguistic techniques construct moral and emotional support for Palestine. Methods: The research adopts a descriptive qualitative design with a critical discourse analysis approach. Data were collected through purposive sampling from 16 images posted on the feeds and stories of six Instagram accounts discussing Palestine. The data consist of phrases and sentence fragments containing persuasive elements. Each item was coded according to Aristotle’s rhetorical strategies (logos, ethos, pathos) and analyzed using linguistic techniques such as repetition, metaphor, synecdoche, irony, and slogan formulation. Results: The study identifies three main persuasion strategies: (1) logos, reflected through evidential claims, rhetorical questions, slogans, repetition, and comparative stylistic devices; (2) ethos, manifested through religious–moral values, irony, metaphors, and sound-play that strengthen the speaker’s credibility; and (3) pathos, expressed through emotional appeals, the synecdoche of “the heart,” and imperative statements encouraging empathy and moral action. Implications: The findings indicate that digital religious discourse significantly contributes to shaping public opinion and strengthening humanitarian advocacy through effective rhetorical strategies. Conclusions: Religious utterances on Instagram combine logic, moral credibility, and emotional appeal to influence audiences. The study recommends further research on digital rhetoric in religious and global conflict discourse.